Resurgence of Cold War (2.0) Rivalry in Latin America: Assessment of US-China Battle for Influence - Rashid, Asma; Amna Shafique (JSSH, 2023)
After successfully surviving and braving the harsh blazing winds coming in from the giant of the eastern hemisphere, US has somehow relegated itself to the same position again but this time with an enemy hell bent on reducing US to dust as far as its title as a superpower is concerned. China is not only reading United States really well to counter it but is bring proactive by anticipating its moves and neutralizing it. China and United States are up against each other in every single field and corner of the world. Wherever one lays foot, the other tries to hoist its flag there. This version of cold war has crept into the South America and Central America which are already suffering politically and economically. United States for a long time incentivized these states to sing its praises by concluding Free Trade Agreements with the Dominican Republic, Costa Rica, El Salvador, Nicaragua, Honduras, Panama, Peru and Mexico. Due to other commitments, the last few decades saw the demotion of these states in the list of US’ priorities therefore limiting its role only to the promotion of security and democratic ideals. Meanwhile China used this opportunity to infiltrate deep into this region by striking Free Trade Agreements of its own with Brazil, Chile, Costa Rica, Per and Uruguay and is in talks with other countries one of which is Ecuador to join the list. This paper holds to pin point and then trace the path of these two major powers in navigating the Latin American front of the Cold War 2.0. It is set to be a qualitative study banking on primary and secondary data by accessing archives, journals, articles, newspaper, magazines, think tanks, policy makers etc.